Genome-Wide Analysis Characterization and Evolution of SBP Genes in Fragaria vesca, Pyrus bretschneideri, Prunus persica and Prunus mume - Abdullah, Muhammad; Cao, Yunpeng; Cheng, Xi; Shakoor, Awais; Su, Xueqiang; Gao, Junshan; Cai, Yongping (Frontiers in Genetics, 2018)
The SQUAMOSA promoter binding protein (SBP)-box proteins are plant-specific transcriptional factors in plants. SBP TFs are known to play important functions in a diverse development process and also related in the process of evolutionary novelties. SBP gene family have been characterized in several plant species, but little is known about molecular evolution, functional divergence and comprehensive study of SBP gene family in Rosacea. We carried out genome-wide investigations and identified 14, 32, 17 and 17 SBP genes from four Rosacea species (Fragaria vesca, Pyrus bretschneideri, Prunus persica and Prunus mume, respectively). According to phylogenetic analysis arranged the SBP protein sequences in seven groups. Localization of SBP genes presented an uneven distribution on corresponding chromosomes of Rosacea species. Our analyses designated that the SBP genes duplication events (segmental and tandem) and divergence. In addition, due to highly conserved structure pattern of SBP genes, recommended that highly conserved region of microsyneteny in the Rosacea species. Type I & II functional divergence was detected among various amino acids in SBP proteins, while there was no positive selection according to substitutional model analysis using PMAL software. These results recommended that the purifying selection might be leading force during the evolution process and dominate conservation of SBP genes in Rosacea species according to environmental selection pressure analysis. Our results will provide basic understanding and foundation for future research insights on the evolution of the SBP genes in Rosacea.